Rodríguez, Félix (2017): Gran diccionario de anglicismos, Madrid, Arco/Libros, 1.142 pp., ISBN 978-84-7635-955-6. (Revista de Lexicografía, 2018)
Reseña de Rodríguez, Félix (2017): Gran diccionario de anglicismos, Madrid, Arco/Libros, 1.142 pp., ISBN 978-84-7635-955-6.